Pengaruh Inovasi Dan Kreativitas Terhadap Kepuasan Konsumen Barber Shop (Lidya) Di Kota Gorontalo - Mohune, Yusup I.; Hafid, Radia; Halid, Risca Marsanti; Bumulo, Frahmawati; Gani, Imam Prawiranegara (Innovative: Journal Of Social Science Research, 2024)
Yusup. I. Mohune Student ID Number 911420066. 2024. “The effect Of Innovation and Creativity On Consumer Satisfaction at Barber Shop (Lidya) ini Gorontalo City”. Undergraduate Thesis, Bachelor’s Degree Program In Economocis, Department Of Economics Education, Universitas Negeri Gorontalo. The principal supervisor is Dr. Radia Hafid, S.Pd., M.Si, anda the co-supervisor is Risca Marsanti Halid, S.Pd., M.Pd. The purpose of this research is to determine the effect of innovation and creativity on consumen satiffaction at Berber Shop (Lidya) in Gorontalo City. This is a quantitative research using Ecpost Faktor research method. The primart data used were obtained by distributing questionnaires to consumers of Barber Shop Lidya Gorontalo City. The sample consists of 93 consumers of Barber Shop Lidya Gorontalo City. The data analysis technique uses multiple linear regression with the help of the SPSS program. The results showed that simultaneously, the variables of Innovation and Creativity signicantly affected customer satisfaction with a significance value of 0,000. Partial test results showed that the variables of Innovation and Creativity contributes a positive effect on customer satisfaction. The coefficient determination of R Square was 0,624 or 62,4%, which means that the two independent variables